Nano material parts for medical analysis machine-applications - Thorsten Hickmann (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2020)
When it comes to application of specific material properties, high accuracy and minimal rework of nano-metal components are the key elements for a sucessful process. The parts can be either produced by Laser melting, or by metal injection moulding, depending on the volumes oft he desired applications.  These nanostructured materials are possible to produce on different material basis, however titanium is preferred. Both options are usable for medical parts. The technology is defined by the numbers of pieces which need to be produced.